The Role of Vocational Education in Logistics and Supply Chain Development - Juliadi, Aldi Adista; Oktirellia, Alya Sophia; Maulana, Yusuf; Sasmita, Asep Hadian; Dwiyanti, Vina (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2021)
Technical and Vocational Education Training (TVET) is one of the institutions that focuses on ready-to-work graduates. This study aims to identify vocational education in logistics and supply chain in producing a workforce that meets logistics industry standards. The research method used is Systematic Literature Review (SLR) using sources from scientific articles published in the last 10 years around 2011 to 2021. The results of the study found that in the development of the logistics program there was a lack of student awareness of the potential and discipline as a career field. The capabilities that must be possessed include logistics curriculum, TVET curriculum, TVET learning, TVET skills, soft skills, technical skills, administrative skills, managerial skills, professional skills, communication skills, technology skills, worker skills, logistics performance. TVET has a central working pattern, collaborates with other institutions, develops a training curve according to field needs, with innovative and sustainable technology and information.